Optimizing the Function of Mosque Tarbiyah: Fostering the Morals of the Young Generation in the Digital Era - Yusuf, Mochamad Giffari; Ulfah, Ulfah (UIN Sunan Gunung Djati Bandung, 2026)
Mosques, as centers of Islamic civilization, play a crucial role in shaping the character of the younger generation, especially in the challenging digital era. This study aims to examine the optimization of the mosque's tarbiyah function in fostering the morals of the younger generation, with a case study at the Al-Ikhlas Mosque in Cibiru, Bandung City. The research method used was qualitative with a case study approach, involving observation, interviews, and documentation. The results show that the Al-Ikhlas Mosque has fulfilled its tarbiyah function through the Madrasah Diniyah Takmiliyah (MDT) program, which serves children from early childhood to adolescence. In addition to the Madrasah Diniyah Takmiliyah, the Al-Ikhlas Mosque also implements a moral development program integrated into worship activities, religious studies, and social activities. These programs are designed to instill Islamic values, improve religious understanding, and shape behavior in accordance with Islamic teachings. Optimisation of the mosque's tarbiyah function is carried out through improving the competence of teachers and administrators, using innovative and participatory learning methods, as well as utilising information technology in the learning process and disseminating positive and inspiring content.